Significant improvement of bone mineral density by denosumab treatment in Japanese osteoporotic patients following breast cancer treatment - Nakamura Y; Kamimura M; Morikawa A; Taguchi A; Suzuki T; Kato H (Dove Medical Press, 2018)
Yukio Nakamura,1,2 Mikio Kamimura,3 Akio Morikawa,4 Akira Taguchi,5 Takako Suzuki,1 Hiroyuki Kato1 1Department of Orthopaedic Surgery, Shinshu University School of Medicine, Matsumoto, 2Department of Orthopedic Surgery, Showa-Inan General Hospital, Komagane, 3Center for Osteoporosis and Spinal Disorders, Kamimura Orthopaedic Clinic, Matsumoto, 4Department of Surgery, Showa-Inan General Hospital, Komagane, 5Department of Oral and Maxillofacial Radiology, School of Dentistry, Matsumoto Dental University, Shiojiri, Japan Background: The aim of this study was to evaluate the effects of denosumab in patients with osteoporosis (OP) and non-metastatic breast cancer following treatment of 1) surgery, 2) surgery and aromatase inhibitors, and 3) surgery, aromatase inhibitors, and anti-cancer agents, compared with those in primary OP patients. Patients and methods: In this retrospective 24-month study, patients were divided into the primary OP group (34 cases) or OP receiving breast cancer treatment group (breast cancer group; 17 cases). We measured serum calcium, whole parathyroid hormone (PTH), 1,25OH2D3, bone alkaline phosphatase (BAP), tartrate-resistant acid phosphatase-5b (TRACP-5b), and bone mineral density (BMD) of the lumbar 1–4 vertebrae (L-BMD) and bilateral total hips (H-BMD) for 24 months. Results: The percent changes of serum calcium in the breast cancer group were significantly lower than those in the primary OP group at 1 week, 1 and 12 months. The percent changes of whole PTH in the primary OP group were significantly lower than those in the breast cancer group at 2 and 4 months. Significant differences were found between the groups at 18 months (-34.5% in the primary OP group and -52.6% in the breast cancer group, respectively) for the percent changes of BAP. Significant differences were found between the groups at 12, 18, and 24 months (-39.7% in the primary OP group and -64.0% in the breast cancer group at 24 months, respectively) for the percent changes of TRACP-5b. The percent changes of L-BMD and H-BMD were significantly increased at 12, 18, and 24 months in both the primary OP group (7.0% and 4.7% at 24 months, respectively) and breast cancer group (8.0% and 5.4% at 24 months, respectively), compared with pre-treatment levels. Significant differences were not found between the groups for the percent changes of L-BMD and H-BMD. Conclusion: Denosumab significantly increased L-BMD and H-BMD to comparable degrees in both groups; therefore, it represents a good therapeutic option for OP receiving breast cancer treatment as well as primary OP. Also, vitamin D supplementation is required due to the potential hypocalcemia, and estrogen may be responsible for the decrease of serum calcium in the breast cancer patients. Keywords: bone mineral density, bone turnover markers, breast cancer, denosumab, osteoporosis